2021
DOI: 10.1007/s00103-021-03371-4
|View full text |Cite
|
Sign up to set email alerts
|

Mundgesundheitskompetenz von Menschen mit Migrationshintergrund – Erste Auswertungen der MuMi-Studie

Abstract: Zusammenfassung Hintergrund Erste Studien heben den Migrationshintergrund von Menschen in Deutschland als eigenständigen Risikofaktor für eine mangelhafte Mundgesundheit hervor. Ein wichtiger Einflussfaktor könnte hierbei eine niedrigere Mundgesundheitskompetenz von Menschen mit Migrationshintergrund sein. Ziel In diesem Artikel werden Ergebnisse zur Mundgesundheitskompetenz und Mundgesundheit aus der MuMi-Studie (Förderung der Mundgesundheit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous research has found that people with chronic diseases and people with migration backgrounds have lower health literacy levels [ 8 , 34 , 35 ]. Such differences, however, were not found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that people with chronic diseases and people with migration backgrounds have lower health literacy levels [ 8 , 34 , 35 ]. Such differences, however, were not found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The Muslim population in Germany has almost exclusively of a migration background [ 71 ]. Recent studies showed that people with a migration background in Germany demonstrated poorer oral health literacy levels and oral health status than people without a migration background [ 73 , 74 ]. Another possible explanation for the differences in OHRQoL in our study might be the lack of knowledge and understanding of the specific needs of Muslim patients among Western healthcare providers [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The poor oral health of people with migration background relates to a lower socio-economic status (SES) [ 42 ] [ 43 ], high intake of sugar-rich beverages (i.e. sweetened tea), low oral health literacy [ 44 ], low and more pain than prevention oriented utilization of dental care services, poor German language skills, and other lifestyle and cultural difference in comparison to the non-migrant population [ 45 ]. In addition, people with migration background often live in socially deprived areas with a low physician-population ratio [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%